Filsafat Pendidikan Anak Usia Dini menurut Ki Hajar Dewantara: Menumbuhkan Karakter, Kemandirian, dan Cinta Belajar Sejak Dini - Rizka Latifa (Alzam: Journal of Islamic Early Childhood Education, 2025)
The Abstract contains a brief description of the purpose of writing, the method used, and the results of the study (if the results of the research). Abstract contains 200-300 words. Abstract written in Indonesian and English. Abstract typing is done single-spaced with narrower margins than the right and left margins of the main text. Keywords need to be included to describe the area of ​​the problem being studied and the main terms that underlie the implementation of the research. Key words can be single words or combinations of words. Number of keywords 3-5 words. These keywords are required for computerization. Searching for research titles and abstracts is made easier with these key words. This study aims to examine the philosophy of early childhood education according to Ki Hajar Dewantara's thoughts, particularly in relation to character development, independence formation, and the cultivation of a love for learning from an early age. Using a qualitative approach and literature review, it was found that the concepts of tuntunan kodrat, among system, and an emphasis on humanistic and contextual education form the core of his philosophy. Children are positioned as active and unique individuals with potentials that must be nurtured through gentle guidance, wisdom, love, and exemplary conduct. Ki Hajar Dewantara’s ideas align with modern educational theories such as Piaget’s constructivism, Vygotsky’s scaffolding, and Gardner’s multiple intelligences, all of which highlight the importance of child-centered education. In conclusion, Ki Hajar Dewantara’s educational philosophy remains highly relevant for developing early childhood education that is meaningful, liberating, and character-based Abstrak: Penelitian ini bertujuan untuk mengkaji filsafat pendidikan anak usia dini menurut pemikiran Ki Hajar Dewantara, khususnya dalam kaitannya dengan penanaman karakter, pembentukan kemandirian, dan penumbuhan semangat belajar sejak usia dini. Melalui pendekatan kualitatif dan kajian literatur, ditemukan bahwa konsep tuntunan kodrat, sistem among, serta penekanan pada pendidikan yang humanistik dan kontekstual menjadi fondasi utama dalam pemikiran beliau. Anak diposisikan sebagai individu yang aktif, unik, dan memiliki potensi yang harus dikembangkan dengan pendekatan yang lembut, penuh hikmah, serta berbasis kasih sayang dan keteladanan. Pemikiran Ki Hajar Dewantara sejalan dengan berbagai teori pendidikan modern, seperti konstruktivisme, scaffolding, dan multiple intelligences, yang semuanya menekankan pentingnya pendidikan yang berorientasi pada anak. Kesimpulannya, filsafat Ki Hajar Dewantara sangat relevan dalam pengembangan pendidikan anak usia dini yang lebih bermakna, membebaskan, dan berkarakter.